Generic reassignments of satyrine butterflies from Colombia and Venezuela (Lepidoptera: Nymphalidae). / Reasignaciones genéricas de mariposas satírinas de Colombia y Venezuela (Lepidoptera: Nymphalidae). - Gonzalo Andrade-C, M.; Viloria, Ángel L.; Henao-Bañol, Efraín R.; Le Crom, Jean-François (Anartia, 2020)
ABSTRACT Four genera of butterflies belonging to the Nymphalidae: Satyrinae are erected, diagnosized, described and discussed in order to reassign ten species recently classified within the genus Magneuptychia Forster, several of which occur in Colombia and Venezuela: Nubila Viloria, Andrade & Henao, gen. nov. (to include Euptychia gera Hewitson, E. metagera Butler, E. moderata Weymer, E. nortia Hewitson, E. purusana Aurivillius and E. segesta Weymer), Macrocissia Viloria, Le Crom & Andrade, gen. nov. (including Neonympha iris C. Felder & R. Felder and Euptychia inani Staudinger), Colombeia Viloria, Andrade & Le Crom, gen. nov. (including Euptychia mycalesis Röber) and Omacha Andrade, Viloria, Henao & Le Crom, gen. nov. (including Magneuptychia pax Huertas, Lamas, Fagua & Willmott). Additionally, Euptychia tiessa Hewitson is transfered to the genus Satyrotaygetis Forster, which is revised. Eleven new combinations are established, one new synonym is proposed and two species are reinstated. RESUMEN Se erigen, diagnostican, describen y discuten cuatro géneros de mariposas pertenecientes a las Nymphalidae, Satyrinae, con el fin de reubicar diez especies recientemente clasificadas dentro del género Magneuptychia Forster, varias de las cuales se encuentran en Colombia y Venezuela: NubilaViloria, Andrade & Henao, gen. nov. (para incluir Euptychia gera Hewitson, E. metagera Butler, E. moderata Weymer, E. nortia Hewitson, E. purusana Aurivillius y E. segesta Weymer), Macrocissia Viloria, Le Crom & Andrade, gen. nov. (incluyendo Neonympha iris C. Felder & R. Felder y Euptychia inani Staudinger), Colombeia Viloria, Andrade & Le Crom, gen. nov. (incluyendo Euptychia mycalesis Röber) y Omacha Andrade, Viloria, Henao & Le Crom, gen. nov. (incluyendo Magneuptychia pax Huertas, Lamas, Fagua & Willmott). Adicionalmente se transfiere Euptychia tiessa Hewitson al género Satyrotaygetis Forster, el cual se revisa. Se establecen once nuevas combinaciones, se propone un nuevo sinónimo y se restituyen dos especies.